English as a Business Lingua Franca: A Discursive Analysis of Business E-Mails. (January 2022) - Roshid, Mohammod Moninoor; Webb, Susan; Chowdhury, Raqib
In the current world of business, English as a Business Lingua Franca (BELF) is used in both spoken and written communication and underpinned by the paradigm of English as a Lingua Franca (ELF). While a number of research studies have been conducted exploring the spoken discourse facets of BELF users, relatively little attention has been paid hitherto to explore BELF written discourse facets, particularly, in business e-mail communication. This article examines how the BELF community discursively practices written discourse in their business e-mails. Data have been drawn from a pool of 92 e-mail messages collected from the business personnel engaged in international communications from five ready-made garments business organizations located in Bangladesh. These e-mails were exchanged between nonnative English speakers working as business personnel in the ready-made garments sector in Bangladesh and their counterparts—including both native and nonnative English speakers employed in six different countries. Applying both qualitative and quantitative content analyses, findings reveal that stylistically the components of e-mail messages are usually personalized, flexible and informal, and similar to ELF spoken discourse rather than ELF academic discourse and/or standard business letter writing. A wide range of language features have been identified in e-mails that are unique in this specific technology-based genre of communication. The awareness of these different facets of e-mail discourse has multiple implications in education.